1999
DOI: 10.1084/jem.189.11.1707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Grb2 As a Novel Binding Partner of  Tumor Necrosis Factor (TNF) Receptor I

Abstract: Tumor necrosis factor α (TNF-α) is a proinflammatory cytokine. Its pleiotropic biological properties are signaled through two distinct cell surface receptors: the TNF receptor type I (TNFR-I) and the TNF receptor type II. Neither of the two receptors possesses tyrosine kinase activity. A large majority of TNF-α–dependent activities can be mediated by TNFR-I. Recently, c-Raf-1 kinase was identified as an intracellular target of a signal transduction cascade initiated by binding of TNF-α to TNFR-I. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…The PreS2-dependent activation of AP-1 or NF-B requires the cytoplasmic localization of the PreS2-domain. 13,14 Moreover, the specific inhibition of the TNF␣-dependent activation of c-Raf-1 kinase by a PreS2-TLM-PLAP fusion peptide competing the Grb2/TNF-RI interaction, which occurs in the cytosolic compartment, 17 confirms that the PreS2-TLM enables the translocation across the membrane. The specificity and effectiveness of these effects is demonstrated by the fact that low concentrations of 2 m protein or peptide added to the culture medium are sufficient to exhibit these intracellular effects, whereas the respective mutants fail to induce these effects.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The PreS2-dependent activation of AP-1 or NF-B requires the cytoplasmic localization of the PreS2-domain. 13,14 Moreover, the specific inhibition of the TNF␣-dependent activation of c-Raf-1 kinase by a PreS2-TLM-PLAP fusion peptide competing the Grb2/TNF-RI interaction, which occurs in the cytosolic compartment, 17 confirms that the PreS2-TLM enables the translocation across the membrane. The specificity and effectiveness of these effects is demonstrated by the fact that low concentrations of 2 m protein or peptide added to the culture medium are sufficient to exhibit these intracellular effects, whereas the respective mutants fail to induce these effects.…”
Section: Discussionmentioning
confidence: 87%
“…In a previous investigation, 17 we observed that this PLAP motif mediates the interaction of TNF-RI with the C-terminal SH3 domain of the adapter molecule Grb2. This Grb2/TNF-RI-interaction is a prerequisite for the TNF␣-dependent activation of c-Raf-1 kinase.…”
Section: Figure 2 the Pres2 Domain Translocates Into The Cytosol Wesmentioning
confidence: 79%
“…It has been shown that Src and adapter proteins Grb2, crk, and p130 Cas are downstream mediators of Pyk2 leading to the activation of p44/p42 MAPK and JNK (48). The association of Grb2 directly with TNFR1 has been reported (49). Thus, it is possible that TNF-induced Syk activation recruits Pyk2, which in turn recruits Grb2, leading to MAPK activation.…”
Section: Discussionmentioning
confidence: 96%
“…185 Further, the adapter protein Grb2 binds to a PLAP motif of TNF-R1, thereby potentially linking this receptor via SOS to Ras, c-Raf and the ERKs. 186 This signal, however, appears not sufficient to efficiently activate the MAP kinases, as FAN/nSMasederived ceramide acting on the ceramide-activated protein kinase (CAP-K; 187 ) is necessary to fully activate c-Raf. 186 Consistent with these data, survival of osteoclasts by TNF is mediated by Akt and ERKs and can be blocked by inhibitors of the ERK-activating kinase MEK-1, but also by a peptide interfering with FAN/PLAP domain interaction.…”
Section: Tradd-independent Signalling Pathwaysmentioning
confidence: 99%